The Role of the Personified ankh in the Offering Scenes of the New Kingdom - Hamden, Ahmed.
Depictions of the personified ankh incorporated in the offering scenes became frequent during the New Kingdom. The main goal of this paper is to propose an adequate view of this important phenomenon and to offer data to interpret its clear role within the context of the gathered scenes in the temples and tombs.